Patients without psychopathology applying for aesthetic rhinoplasty may display elevated harm avoidance and reduced self-directedness: a cross-sectional, case-control study - Gurok, Mehmet Gurkan; Kilic, Faruk; Saglam, Sema; Gurok, Nese Gocer; Kuloglu, M. Murat; Yildirim, Alpagan M. (Taylor & Francis Ltd, 2019)
Objective The present study was intended to compare the body image, self-esteem, temperament and character traits of a group of patients who applied for aesthetic rhinoplasty with healthy controls subjects. Methods Thirty patients who applied the Plastic, Reconstructive and Aesthetic Surgery Clinic at the Firat University Hospital for aesthetic surgery were included in the present study. In addition, thirty healthy individuals who met the study criteria and were matched the patient group by age and gender were included in the study as the healthy control group. Temperament and Character Inventory (TCI), body image (BI) scale, The Rosenberg Self-Esteem Scale (RSES), and sociodemographic data form were applied to patient and control groups. Results The patients with aesthetic rhinoplasty had higher body image (BI) scores compared to the control group (t = 2.828, p = .006), and had higher novelty seeking (NS) (p = .038) and lower harm avoidance (HA) scores for temperament dimensions. The outcomes of the correlation analysis yielded a positive correlation between the RSES and BP scores and the HA temperament subscale scores were positively correlated with RSES (r = 0.389, p = .033) and BP (r = 0.461, p = .010) scores. In addition, a negative correlation (r = -0.496, p = .005) was determined between the RSES scores and self-directedness (SD), which is a character subdimension. Conclusion The present study established that there existed differences in the aesthetic rhinoplasty patient group in terms of body image, self-esteem, temperament and character traits. The differences in temperament traits could indicate that the condition is hereditary. Determining such differences was considered significant for both identifying patients as candidates for surgery and predicting the level of satisfaction from surgery. In order to obtain better results, it is required to perform longitudinal studies with larger sample.
Keywords: Aesthetic rhinoplasty; temperament; character; self-esteem; body image